Corruption and its alternatives: A takeoff theory of good governance - Evan Osborne (Osaka University, Institute of Social and Economic Research (ISER), 2004)
Corruption is a function of its return relative to engaging in productive activities. This paper presents an approach for thinking about the institutional features of societies and the resulting amount of corruption. The empirical results suggest that political competition is more important than competition in information-producing industries. The rent-seeking view of the relation between government and corruption is rejected in favor of the Becker (1983) model of political competition. The paper suggests that societies that continually stay open to productivity-enhancing activities will eventually enter a takeoff stage of anti-corruption efforts analogous to the eventual improvement in income distribution that occurs in successful industrialization.
Keywords: 330; Korruption; Neue politische Ökonomie; Theorie; Technischer Fortschritt; Good Governance